THE USE OF THE WORLD’S SEVEN WONDERS PICTURES TO TEACH DESCRIPTIVE WRITING TO TENTH GRADERS (RETAIN, 2014)
THE USE OF THE WORLD’S SEVEN WONDERS PICTURES TO TEACH DESCRIPTIVE WRITING TO TENTH GRADERS Nindia Dara Kartika English Department, Language and Arts Faculty, State University of Surabaya nindiadara@yahoo.com Fahri English Department, Language and Arts Faculty, State University of Surabaya fahriahli267@yahoo.co.id Abstract The present study aims to teach how does the implementation of the world’s seven wonders pictures, how their results, and how their responses. This study is descriptive qualitative. The tenth graders of SMA NEGERI 19 Surabaya are the subjects of the study. The data was gained through observation checklists and field notes, the students’ writing compositions, and questionnaire. The research was conducted in two meeting. In every meeting the teacher gave them task in groups. From the result of the study, the use of the world’s seven wonders pictures help the students to encourage and stimulate their writing ability in producing written descriptive text easily and properly based on the generic structure and linguistic features. It can be proved from the progression of students’ writing which scored in the term of each component. Thus, it can be concluded that the use of the world’s seven wonders pictures was run well, because the students had progression in their writing ability. Keywords: the world’s seven wonders pictures, teach, and descriptive writing. Abstrak Penelitian ini bertujuan untuk mengajarkan tentang bagaimana mengimplementasi media tujuh keajaiban dunia, lalu bagaimana hasil siswa, dan bagaimana tanggapan mereka setelah diajari. Penelitian ini adalah deskriptif kualitatif. Subjek dari penelitian ini adalah siswa kelas X SMA NEGERI 19 Surabaya. Data diperoleh melalui observasi ceklis dan catatan, hasil komposisi menulis siswa, dan kuesioner. Penelitian ini dilakukan dalam dua pertemuan. Dalam setiap pertemuan, guru memberikan siswa tugas secara berkelompok. Dari hasil penelitian, penggunaan media tujuh keajaiban dunia dapat membantu siswa mendorong dan merangsang kemampuan menulis mereka di dalam menghasilkan tulisan teks deskripsi dengan mudah dan baik berdasarkan struktur umum dan unsur kebahasaan. Itu dapat dibuktikan dari kemajuan hasil menulis siswa yang dinilai sesuai dengan tiap komponen. Jadi, hal ini dapat disimpulkan bahwa penggunaan mediagambar tujuh keajaiban dunia telah berjalan dengan baik, karena siswa mengalami kemajuan pada kemampuan menulis mereka. Kata kunci: gambar tujuh keajaiban dunia, mengajar, dan tulisan deskripsi. INTRODUCTION Educational problems always occur together with developing and increasing the ability of students, situations and environmental conditions, the influence of information and culture, and also the development of science and technology. In essence, the main function of language is a communication. Communication is a process of transferring information form one entity to another. Communication holds the important act for people to socialize with others. Thus, a good communication will bring somebody into a good life. There are two ways of communication, verbal and nonverbal communication. Mehrabian says that verbal communication impact more than fifty percents by nonverbal communication (1967: 248). LaRoche puts writing a skill that ensures students success in every aspect of learning and successes (LaRoche: 2004). Raimes (1983) added that writing also helps students in learning language skills. Joel Salzman simply defines writing as a taking on paper (Salzman on LaRoche: 2001). But it is not simply speech written down on paper. People must learn it. It must be someone to teach it. It is because people learn to speak the first language at home without systematic instruction, where as they are taught at school to write (Raimes: 1983). Moreover, sometimes the students face the difficulties in writing. For instance, writing a descriptive text, it is as one of the aspects of language is actually very necessary in daily life . Writing a description is not only because of academic demands , but also because of the demands of everyday life. Indirectly, in fact we often writing descriptive paragraphs about something or event. For example, when we are in love, we often describe people that we love with the right choice of words. Generally, the men will describe the women who they love specifically, such as about hair , smile , expression, behavior, body shape, and etc. All this overview make the people can imagine the real object someone’s profile easily. However, when the students were asked to create a descriptive paragraph, generally they will encounter obstacles due to hit by a number of concepts and rules that must be understood or followed. Students must write a descriptive paragraph systematically based on the the teacher’s formats. Whereas, sometimes descriptive paragraphs examples given are also very abstract and not at all known to the students. So, how could the students can imagine the description penguins for example, because they seldom or almost never see the real object or drawing penguins. Another case, when the students were assigned to make an overview of their headmaster who is getting mad, definitely they will be able to write descriptive paragraphs with his own style as soon. Constraints in writing descriptive paragraph can actually be overcome with the help of media in learning activities. Using media in learning activities is very important for teachers. The benefit of using media is media helps to enhance the quality in learning. Using media can support the teachers’ materials. Well-designed material takes the wisdom of different accepted learning theorist into account which result in active and effective learning (Kumar, 1998:7). As a result, media is an integral part of the learning activities in order to achieve educational goals. The world’s seven wonders pictures are one of kind of media that can be used for teachers to teach writing about descriptive text. If the students were assigned to make a paragraph description of The Great Wall of China, for example, they would be more easily complete the paragraph when provided an interesting picture. The students easily present the description of The Great Wall of China spesifically, because of the media available. Besides, the students will easily describe the history of that building, the shape, the length and width, the characteristics, and so on. A study of Indah Estu Wilujeng (2008) has elaborated the effectiveness of using pictures in teaching and learning of writing. Her study entitled Pictorial Stories Implementation to Improve the Sixth Grade Students’ Writing Ability at MI Darun Najah Jatirejo Mojokerto. She formulated her research questions as follows: (1) How are the procedures of using pictorial stories in teavhing writing to the sixth grade students of MI Darun Najah Jatirejo Mojokerto? and, (2) Can the implementation of teaching writing using pictorial stories improve the sixth grade students’ writing ability?. At the end of her study, she found that the students had significant improvement from the 1ˢͭ cycle to the last cycle. She believed that the teachnique of presenting pictorial stories in teaching writing was effective and efficient in motivating and increasing the students’ writing ability. In this study, the writer focuses on using pictures of seven wonders of the world for descriptive writing, in which the descriptive has an aim to provide clear descriptions about a certain thing. By using pictures, they display the ideas in visual form. It can helps the students in describing something. Pictures are used in the writing class to help the students in finding her idea and generate it for their writing. This fact will help the teacher in guiding the teaching and learning process while using pictures. METHODS This study is a descriptive qualitative research, because the main aims of the technique are to describe and to explain a natural phenomenon: what is happening?, what is it happening?, why is it happening?, and how is it happening? (Chariri, 2009:9). It is suitable with the objectives of this research, they are to describe the implementation of the world’s seven wonders pictures in writing activity, the students’ writing results, and the students’ responses. The data of a qualitative research are served as interview transcript, field notes, photo, video recording, memo or writing (Hasan, 1990; 27). Thus, the writer is only used the observation checklists and field notes, the questionnaires, and the students’ writing composition. The students of X MIA 6 of SMA NEGERI 19 Surabaya were the participant of this study. It was based on the consideration that they had a distinct demand of curriculum with the eleventh and twelve, that the students are supposed to learn how to write descriptive easily in a specific time allocation was. The data were collected to answer how the implementation of the World’s Seven Wonders Pictures to teach the tenth graders to write descriptive text. There are three sets of data to analyze. The first is the teacher actions as well as the student learning activities during the class, then the second is the students’ responses toward the implementation through their opinions, and the last is the students’ writing compositions. The first data were covered by a set of observation. The observation recorded the teacher’s actions as well as the students’ learning activities responding to what the teacher does, starting from the beginning until the end of the class. It was then followed by observations on some aspects of the teaching materials. The data, gained using checklist and field note, are to answer the first research question. The second data was taken when the researcher passes a close-structured questionnaire to each student. It captured the students’ opinions toward the teaching implementation. This was then to be brought to describe the students’ responses, in regard to answer the second research question. The third data was the data in the form of ESL Composition Profile was used to find out the relation of the topic with the content, through the students’ writing composition. This data is to answer the third research question RESULTS How is the results of the tenth grade students of SMA Negeri 19 Surabaya after being taught by using the world’s seven wonders pictures? The result of students' writing composition was used to know that the implementation of picture puzzle helped the students in writing descriptive text. The researcher collected the students' writing composition from the first and second-day implementation. In this case, the researcher suggested grading the students' writing by using ESL Composition Profile. There were five components of ESL Composition Profile; content, organization, vocabulary, language use, and mechanics: Each component was categorized into four criteria. Those criteria were excellent to very good, good to average, fair to poor, and very poor. Here were analysis and example of students’ writing composition in first and second meeting. Organization was become one of the important component which we must be concerned in writing. It was scored based on how well organized, fluent expression ideas, good understanding of generic structure, logical sequencing, and cohesive the students organized the composition. Here, the reseacher discussed and gave example of student’s composition that improved in term of organization in first meeting. From the text above, the organization component was excellent to very good because the text had given good understanding of generic structure, one sentence to another sentences were related each other, and well organized. Then, the reseacher gave another example of the student’s writing composition which scored in very poor in term of vocabulary in first meeting. Vocabulary was also part of important component in writing, because in vocabulary dealt word/ idiom choice and usage, word from mastery, and appropriate registeer used. Here was the example of the student’s writing composition in term of vocabulary. From the text above, the vocabulary component was very poor because the text had given little knowledge of English vocabulary, such verb; adjective; adverbial, and the ideas not enough to evaluate. Beside, the researcher gave another example of the student’s writing composition which in term of language use component. The component of language use dealt with tense, number, word order or function, articles, pronouns, and preposition. Since, the composition analyzed was descriptive text, the evaluation of language use included the use of simple present tense, subjective opinions, abstract nouns, adverbs, modals, connective, emotive words, compound and complex compound. Here was the example of the student’s writing composition in term of language use component in first meeting. From the text above, the language use component was fair to poor because the text had major problems in simple construction, frequent errors of agreement, incorrect of tense (Simple Present Tense). Like in the text, which was incorrected of generic structure. Then, the tense should be used Simple Present Tense, but in the text the students used Past Continuous. Moreover, the reseacher gave another example of the student’s writing composition that improved in term of content in seond meeting. Content was an important component in composition, since it conveyed the main ideas of the writer, The criteria were how knowledgeable the text, given complete important ideas and supporting details, and relevant to assigned topic/ genre are. Here, the reseacher gave the example of the student’s writing composition which improved in term of content component. It can be seen from the text above that the content component was good to average because the text was giving some knowledge of subject and adequate important ideas. Furthermore, the students should pay attention to another components in writing composition, that was mechanics, so that their writing composition readable. It dealt with mastery of convention, spelling, punctuation, capitalization, and paragraphing. Here was the example of the student’s writing composition which improved in term of mechanics component. From the text above, it can be seen that the mechanics component was excellent to very because the text was demonstrated mastery of convention, but still hade few errors of spelling. Like in the text, it is written of the word “Jawa”, it should be “Java”, and the word “Supa” in the text, it should be “Stupa”. From the explanation above, it was shown that the students had progression in their writing. Most group of students could create better composition than previous writing. It can be said that “The World’s Seven Wonders Pictures” was appropriate aid to teach descriptive writing to the tenth graders to help them stimulate their ideas to write desciptive writing easily. CONCLUSIONS Having analyzed the whole data in the previous chapter, the reseacher summarizes the result if this research as follows: 1.The implementation did run well. The teacher had successfully conducted the class to have all activities that were outlined in the lesson plan. 2.After helping the teacher in analyzing data obtained during the research, the reseacher concluded that pictures were effective and useful in helping the students to compose descriptive texts. The advantages offered by this media could motivate the students’ willingness to write. The students were always enthusiastic whenever the teacher shared different pictures in each meeting. In short, the goals expected by both the teacher and the reseacher are completely reached. 3.At the end of the second meeting, the students had reached the better score. In short, the reseacher concluded that this study had successfully achieved its goals by seeing them from the teaching and learning process and the students’ achievement. REFERENCES Hasan, Zaini M. 1990. Karakteristik Penelitian Kualitatif. Malang: Yayasan Asah Asih Asuh. LaRoche, Kelly Morisson. 1993. A Focus on Prewriting and Knowledge Level Strategies and Skills to Improve the Attitudes and Writing Skills of Middle School Students (report). Practicum Report. Nova University Reimer, Casey Nicolle. 2001. Strategies for Writing to Primary Students Using the Writing Process. Master’s thesis. Biola University Raimes, Ann. 1983. Technique in Teaching Writing. New York: Oxford University Press Wilujeng, Indah. (2008). Pictorial Stories Implementation to Improve the Sixth Grade Students’ Writing Ability at MI Darun Najah Jatirejo Mojokerto (Unpublished S-1 Skripsi). State University of Surabaya